Human Parvovirus B19 Seroposıtivity in Multiple Sclerosis Patients With Arthralgia - Berilgen, M.said; Bulut, Serpil; Akbulut, Handan; Kansız, Fatma; Kamanlı, Ayhan (Fırat University, 2004)
Objectives: The aim of this study is to investigate human parvovirus B19 (HPV B19) seropositivity in the multiple sclerosis (MS) patients with widespread arthralgia complaint. Material & methods: The study group consisted of 23 patients with relapsing-remitting MS (RR-MS), not receiving interferon treatment for prophylactic purpose, having an Extended Disability Status Score (EDSS) less than 3 and having no local or systemically diseases which may lead to arthralgia. The control group consisted of 21 cases matched according to age and sex. The levels of anti-HPV IgG and IgM were examined in sera of patients and control groups. Results: The levels of anti-HPV IgG and IgM in sera were not differing significantly between the patients with MS versus control group. Conclusion: Although anti-HPV B19 IgG and IgM antibody levels were higher in MS patients, this difference between MS and control groups was not statistically significant. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Çalışmamızda yaygın artralji şikayeti olan multiple skleroz (MS) hastalarında serum Human Parvovirus B 19 ( HPV) seropositifliğini araştırmayı amaçladık. Gereç ve Yöntem: Hasta grubu relapsing-remitting multiple skleroz (RR-MS) tanısı alan ve herhangi bir koruyucu tedavi almayan ve Extended Disability Status Score (EDSS) 3 den az olan 23 kişiden oluşturuldu. Bu hastaların tümünde artralji şikayeti mevcuttu ve artralji yapabilecek sistemik ve lokal bir hastalık saptanmamıştı. Kontrol grubu yaş ve cinsiyet uyumlu 21 kişiden oluşturuldu. Hasta ve kontrol grubunun serumlarında anti-HPV IgG ve IgM seviyeleri ölçüldü. Bulgular ve Sonuç: Hasta ve kontrol grubu serumlarında anti-HPV IgG ve IgM seviyeleri arasında istatistiksel olarak bir anlamlılık saptanmadı. Yaygın artralji şikayeti olan RR-MS hasta grubunda serum anti-HPV IgG ve IgM seviyeleri kontrol grubuna göre daha yüksek düzeylerde bulunmasına karşın istatistiksel olarak bir anlamlılık saptanmadı. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Artralji Yakınmalı Multiple Sklerosis Hastalarında Serum Human Parvovirus B19 Seropozitifliği